Analysis of Foreign Experiences in Organizing the Landscape of Preschool Educational Institutions - qizi, Musayeva Zumrad Muhitdin (European Journal of Life Safety and Stability (2660-9630), 2022)
This article explores and analyzes foreign experience in landscape planning in preschool educational institutions.